Development and evaluation of biodegradable silk fibroin scaffolds - E. I. Podbolotova; L. A. Kirsanova; E. G. Kuznetsova; N. V. Grudinin; A. R. Pashutin; O. I. Agapova; A. E. Efimov; E. A. Nemets; Yu. B. Basok; I. I. Agapov (Вестник трансплантологии и искусственных органов)
Objective: to investigate the biodegradation of natural silk-based tissue scaffolds (NS-TS) under in vitro and in vivo conditions, assessing their potential for tissue engineering applications.Materials and methods. Two types of NS-TS, Fibroplen-Atlas and Fibroplen-Gas, along with their modified versions, were analyzed. In vitro biodegradation was assessed in Fenton’s solution, while in vivo studies were conducted on rats, with histological and morphometric analysis of the implants at 4, 14, and 56 days post-implantation.Results. In vitro biodegrada- tion studies showed that Fibroplen-Gas completely degraded in <15 days, whereas Fibroplen-Atlas persisted for up to 45 days. In vivo analysis showed gradual resorption of all scaffolds, with Fibroplen-Gas exhibiting more pronounced degradation. Histological examination revealed a macrophage response, formation of foreign-body giant cells, and signs of implant vascularization. Morphometry confirmed a reduction in filament cross-sectional area, particularly in modified samples.Conclusion. Modifications of NS-TS influence their biodegradation rate, inflammatory response, and vascularization.